Substrate Integrated Slot Array Antenna with Required Radiation Pattern Envelope - M. M. Zhou; Y. J. Cheng; W. N. Huang (International Journal of Antennas and Propagation)
A substrate integrated slot array antenna with a prescribed radiation pattern is investigated in this paper. To meet the requirement of a certain standard radiation pattern envelope, the array configuration and the element excitation coefficient should be considered together. An efficient and systematic method is proposed to determine the element number and element weights in a planar array. After that, the geometrical dimension of the substrate integrated slot array can be synthesized. As an example, a K-band 16 × 22 slot array antenna based on the substrate integrated waveguide (SIW) technology is designed, fabricated, and measured. Its radiation pattern can meet the class 3 antenna radiation pattern envelope of the European Telecommunications Standards Institute (ETSI) standard pattern. Experimental results are in good agreement with simulated ones.